C9orf72 hexanucleotide repeat allele tagging SNPs: Associations with ALS risk and longevity - Kaivola, Karri; Pirinen, Matti; Laaksovirta, Hannu; Jansson, Lilja; Rautila, Osma; Launes, Jyrki; Hokkanen, Laura; Lahti, Jari; Eriksson, Johan G.; Strandberg, Timo E.; FinnGen,; Tienari, Pentti J. (Frontiers in Genetics, 2023)
C9orf72 hexanucleotide repeat expansion (HRE) is a common cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). The C9orf72 locus may harbor residual risk outside the HRE, but the evidence is conflicting. Here, we compared 683 unrelated ALS cases and 3,196 controls with Finnish ancestry to find best single nucleotide polymorphisms (SNP) that tag the C9orf72 HRE and intermediate-length alleles. Rs2814707 was the best tagging SNP for intermediate-length alleles with ≥7 repeats (p=5 x 10-307) and rs139185008 for the HRE (p=7 x 10-114). Rs139185008 also tagged intermediate-length alleles with ≥20 repeats. Carriership of rs139185008*C was associated with ALS also after removing cases with the HRE (p=0.001, OR=2.15) and when considering a subpopulation homozygous for the rs2814707*T (p= 0.00067, OR=4.59). We then leveraged Finnish biobank data via FinnGen to test the effects of rs2814707 and rs139185008 on survival by analyzing their frequencies in age groups <50, 50-80 and >80 years after removing individuals with ALS/FTD diagnoses. The frequency of rs139185008*C heterozygotes decreased significantly with age in the comparisons between 50-80 years vs. >80 years (p=0.0005) and <50 yrs vs. >80 yrs (p=0.0001). These findings were replicated in a smaller cohort from FinnGen (2-sided p=0.037 in 50-80 years vs. >80 years and 0.061 in <50 years vs. >80 years comparison). We did not detect significant survival effect in rs2814707*T homozygotes. Our case-control analysis support residual risk at the C9orf72 rs139185008*C haplotype other than the HRE. The haplotype’s decreasing frequency in aging suggests association with age-related diseases probably also outside ALS/FTD.